Safety of multiple intravenous infusions of adipose-derived mesenchymal stem cells for hospitalized cases of COVID-19: a randomized controlled trial - de Dios, Constanza; Vij, Ridhima; Kim, Hosu; Park, Hyeonggeun; Chang, Donna (Frontiers in Medicine, 2023)
The purpose of the study was to assess the safety of allogeneic, Hope Biosciences Adipose Derived Mesenchymal Stem Cells (HB-adMSCs) for the treatment of hospitalized subjects with COVID-19.Methods: N=48 patients were randomly assigned to HB-adMSC (100 MM) or placebo group. Four intravenous infusions of HB-adMSCs or saline were administered at days 0, 3, 7, 10. The primary safety endpoint was incidence of adverse and serious adverse events (AE/SAEs); secondary endpoints were incidence of specific AEs and alterations in hematology, biochemistry, and coagulation parameters.Results: Majority of AEs were mild in severity. HB-adMSC group showed a higher incidence of cardiopulmonary failure, anemia, anxiety, and diarrhea, while placebo group showed a higher incidence of headaches, fatigue, and chest discomfort (posterior probabilities ≥80%). Deaths were attributed to severe complications due to COVID-19 and were unrelated to study drug. No AEs were attributed to the treatment. Hematology and coagulation panel alterations were not associated with HB-adMSCs. Analyses of inflammatory markers showed increased levels of interleukin-6 and Creactive protein over time in HB-adMSC group (posterior probabilities ≥78%).Multiple infusions of 100MM allogeneic HB-adMSCs were considered safe for the study population. More research is needed to determine the safety of MSC therapy.